hTERT gene methylation in circulating DNA, tumor, and surrounding tissue in breast cancer: a prospective study - Queiroz, Luiz Fernando de; Silva, Marcelo Soares da Mota e; Souza, Heitor Siffert Pereira de; Rosas, Siane Lopes Bittencourt; Carvalho, Maria da Glória da Costa (São Paulo Medical Journal, 2025)
BACKGROUND: The human telomerase reverse transcriptase (hTERT) enzyme, encoded by the hTERT gene, synthesizes protective telomeric sequences on chromosomes and plays a fundamental role in cancer formation. Methylation of the hTERT gene has an upregulatory effect, increasing hTERT enzyme synthesis and allowing continuous tumor cell division. OBJECTIVE: In a group of patients with breast cancer, we aimed to analyze the methylation status of hTERT in the tumor, surrounding tissue, and circulating free deoxyribonucleic acid (cfDNA) of blood collected on the day of mastectomy and then approximately one year later. DESIGN AND SETTING: A prospective study was conducted at a university hospital in Rio de Janeiro, Brazil. METHODS: Samples were collected from 15 women with breast cancer on the day of mastectomy and approximately one year postoperatively. cfDNA was analyzed by sodium bisulfite conversion, followed by polymerase chain reaction, electrophoresis, and silver nitrate staining. RESULTS: Methylation of hTERT was detected in the tumors and surrounding tissues of all 15 patients. Five patients displayed hTERT methylation in the cfDNA from the blood of the first collection. Of the ten patients who returned for the second collection, three showed methylation. Two patients with methylation in the first collection did not display methylation in the second collection. One patient with no methylation in the first collection displayed methylation in the second collection, and one patient had a diminished level of methylation in the second collection. CONCLUSION: Only one-third of patients displayed methylation in their cfDNA, which may be related to the success of chemotherapy.